Human height and weight classification based on footprint using gabor wavelet and K-NN methods - Ryan Bagus Wicaksono; Suci Aulia; Sugondo Hadiyoso; Bambang Hidayat (LPPM INSTITUT TEKNOLOGI TELKOM PURWOKERTO, 2022)
Height and weight are parameters to identify a person, especially for a forensic. To identify height and weight is usually done manually. In addition to manually using height measuring devices and scales, you can also use information related to the foot length. There is a relationship between height and foot length can be expressed in the correlation coefficient (r) as same as for weight. Therefore, in this study, a system for measuring human height and weight based on images of the footprint is implemented on Android. The methods used in this study are Gabor Wavelet and k-Nearest Neighbor (k-NN). The simulation results generate the best accuracy of 75%. The system can also used to categorize the ideal body level according to the Body Mass Index (BMI). The system is able to process images with an average computation time of 8.92 seconds.